2021
DOI: 10.1111/cdev.13504
|View full text |Cite|
|
Sign up to set email alerts
|

Capturing Environmental Dimensions of Adversity and Resources in the Context of Poverty Across Infancy Through Early Adolescence: A Moderated Nonlinear Factor Model

Abstract: Income, education, and cumulative‐risk indices likely obscure meaningful heterogeneity in the mechanisms through which poverty impacts child outcomes. This study draws from contemporary theory to specify multiple dimensions of poverty‐related adversity and resources, with the aim of better capturing these nuances. Using data from the Family Life Project (N = 1,292), we leveraged moderated nonlinear factor analysis (Bauer, 2017) to establish group‐ and longitudinally invariant environmental measures from infanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…In addition, it will be important to assess individual-level networks ( Seitzman et al, 2019 ), to see whether network boundaries differ meaningfully as a function of children’s experiences. Further, it would be interesting to determine which specific aspects of children's home environment underlie the effects reported here, given that experiences differ markedly even among children living in poverty ( DeJoseph et al, 2021 , Ellwood-Lowe et al, 2021 , Humphreys and Zeanah, 2015 , McLaughlin et al, 2014 , Rakesh et al, 2021 , Rakesh et al, 2021 ). While the differential patterns of brain activity we see here may reflect years of childhood experiences, other research has shown that rs-fMRI changes as a function of even brief experiences, even in adulthood ( Guerra-Carrillo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it will be important to assess individual-level networks ( Seitzman et al, 2019 ), to see whether network boundaries differ meaningfully as a function of children’s experiences. Further, it would be interesting to determine which specific aspects of children's home environment underlie the effects reported here, given that experiences differ markedly even among children living in poverty ( DeJoseph et al, 2021 , Ellwood-Lowe et al, 2021 , Humphreys and Zeanah, 2015 , McLaughlin et al, 2014 , Rakesh et al, 2021 , Rakesh et al, 2021 ). While the differential patterns of brain activity we see here may reflect years of childhood experiences, other research has shown that rs-fMRI changes as a function of even brief experiences, even in adulthood ( Guerra-Carrillo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, those who were retained may be considered to have at least some interest in child development (because they were willing to take part in this study) and may, therefore, be more likely to engage in enriching activities with their child, which may have distorted our results. We also note that broad indicators such as income and parental education mask considerable heterogeneity, and may not have the same meaning across nations or racial-ethnic groups (DeJoseph et al, 2021).…”
Section: Limitationsmentioning
confidence: 96%
“…In addition, it will be important to assess individual-level networks (Seitzman et al, 2019), to see whether network boundaries differ meaningfully as a function of children's experiences. Further, it would be interesting to determine which specific aspects of children's home environment underlie the effects reported here, given that experiences differ markedly even among children living in poverty (DeJoseph et al, 2021;Ellwood-Lowe et al, 2021;Humphreys & Zeanah, 2015;McLaughlin et al, 2014;Rakesh, Seguin, et al, 2021;. While the differential patterns of brain activity we see here may reflect years of childhood experiences, other research has shown that rs-fMRI changes as a function of even brief experiences, even in adulthood (Guerra-Carrillo et al, 2014).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 79%